Increased left ventricular myocardial extracellular volume is associated with longer cardiopulmonary bypass times, biventricular enlargement and reduced exercise tolerance in children after repair of Tetralogy of Fallot. Issue 1 (January 2017) - Riesenkampff, Eugénie; Luining, Wietske; Seed, Mike; Chungsomprasong, Paweena; Manlhiot, Cedric; Elders, Bernadette; McCrindle, Brian; Yoo, Shi-Joon; Grosse-Wortmann, Lars
Abstract Background Unfavorable left ventricular (LV) remodelling may be associated with adverse outcomes after Tetralogy of Fallot (TOF) repair. We sought to assess T1 cardiovascular magnetic resonance (CMR) markers of diffuse LV myocardial fibrosis in children after TOF repair, and associated factors. Methods In this prospective, cross-sectional study, native (=non-contrast) T1 times and extracellular volume fraction (ECV) were quantified in the LV myocardium using CMR. Results were related to ventricular volumes and function, degree of pulmonary regurgitation, as well as surgical characteristics, and exercise capacity. Results There was no difference in native T1 times or ECV between 31 TOF patients (age at CMR 13.9 ± 2.4 years, 19 male) and 15 controls (age at CMR 13.4 ± 2.6 years, 7 male). Female TOF patients had higher ECVs than males (25.2 ± 2.9 % versus 22.7 ± 3.3 %, p  < 0.05). In the patient group, higher native T1 and ECV correlated with higher Z-Scores of right and left ventricular end-diastolic volumes, but not with reduced left and right ventricular ejection fraction or higher pulmonary regurgitation fraction. Longer cardiopulmonary bypass and aortic cross clamp times at surgery correlated with increased native T1 times and ECVs (r  = 0.48, p  < 0.05 andr  = 0.65, p  < 0.01, respectively). Maximum workload (percent of predicted for normal) correlated inversely with ECV (r  = -0.62, p  < 0.05). Higher native T1 times correlated with worse LV longitudinal (r  = 0.50, p  < 0.05) and mid short axis circumferential strain (r  = 0.38, p  < 0.05). Conclusions As compared to controls, TOF patients did not express higher markers of diffuse fibrosis. Longer cardiopulmonary bypass and aortic cross clamp times at surgery as well as biventricular enlargement and reduced exercise tolerance are associated with markers of diffuse myocardial fibrosis after TOF repair. Female patients have higher markers of diffuse myocardial fibrosis than males.